Psychometric properties of the Satisfaction with Life Scale in young Brazilian adults - Souza Silva, Bianca Nubia [UNESP]; Campos, Lucas Arrais de; Silva, Wanderson Roberto da [UNESP]; Maroco, Joao; Duarte Bonini Campos, Juliana Alvares [UNESP] (Cadernos Saude Publica, 2021)
The Satisfaction with Life Scale (SWLS) was originally proposed in the English language to measure the individual's overall perception in relation to life. The study aims to evaluate the psychometric properties of SWLS when applied to young adults and estimate the influence of demographic characteristics on life satisfaction, in a non-probabilistic sample of young adult individuals (18 to 35 years) of both sexes in Araraquara, Sao Paulo State, Brazil. We assessed the fit of SWLS to the data by confirmatory analysis, using the comparative fit index (CFI), Tucker-Lewis index (TLI), and standardized root mean square residual (SRMR). Reliability was estimated by the alpha ordinal coefficient and omega. Factor invariance was estimated by multigroup analysis, with CFI test of statistical difference (Delta CFI). Comparison of the mean scores on satisfaction with life according to sex, age, economic stratum, and employment status was performed with analysis of variance (ANOVA). Participation included 2,170 individuals (females: 67.8%; age: 22.09 years). The model's fit to the different samples was adequate (CFI = 0.981-0.998; TLI = 0.962-0.996; SRMR = 0.026-0.040; omega = 0.842-0.869; alpha = 0.862-0.889). Strict invariance was seen for the target variables. Life satisfaction was greater among individuals in higher economic strata. The data obtained with SWLS were valid, reliable, and invariant between samples with different sex, age, economic strata, and employment status. Life satisfaction was greater among individuals from higher economic strata and did not differ by sex, age, or employment status.
Keywords: Adult; Personal Satisfaction; Psychometrics